The Proto-Hassuna Pottery of the Upper Tigris Basin, Evidence from Sumaki Höyük - Sidar Gündüzalp (Anadolu Araştırmaları)
The emergence of pottery has been regarded as the hallmark of the cultural changes explicitly related to the late 8th and the first quarter of the 7th millennium BCE in Southwest Asia. Accordingly, the initial pottery; mineral-tempered, holemouth-shaped, burnished and dark-surfaced vessels with lugs close to the mouth on both sides, appeared almost simultaneously in a series of settlements in Upper Mesopotamia and the Northern Levant in the first quarter of the 7th millennium BCE. Pottery production increased in the second quarter of the millennium, followed by the appearance of plant-tempered pottery after ca. 6.500 BCE. Plant-tempered pottery, spreading throughout Southwest Asia, symbolizes the diversification of pottery as much as we can speak of regional traditions. This study aims to define plant-tempered Proto-Hassuna pottery from Sumaki Höyük, located in the Upper Tigris Basin, to understand better the similarities and differences between the initial mineral-tempered and plant-tempered pottery groups, thus pointing out the possible regional characteristics of the assemblage.